Effects of urban eutrophication on pelagic habitat capacity in the Southern California Bight - Frieder, Christina A.; Kessouri, Fayçal; Ho, Minna; Sutula, Martha; Bianchi, Daniele; McWilliams, James C.; Deutsch, Curtis; Howard, Evan (Frontiers in Marine Science, 2024)
Land-based nutrient inputs to the ocean have been linked to increased coastal productivity, subsurface acidification and O 2 loss, even in upwelling systems like the Southern California Bight. However, whether eutrophication alters the capacity to support key taxa has yet to be evaluated for this region. Here, we assess the impact of land-based nutrient inputs on the availability of aerobic and calcifying habitat for key pelagic taxa using ocean model simulations. We find that acute, lethal conditions are not commonly induced in epipelagic surface waters, but that sublethal, ecologically relevant changes are pervasive. Land-based nutrient inputs reduce the potential aerobic and calcifier habitat during late summer, when viable habitat is at its seasonal minimum. A region of annually recurring habitat compression is predicted 30 -90 km from the mainland, southeast of Santa Catalina Island. Here, both aerobic and calcifier habitat is vertically compressed by, on average, 25%, but can be as much as 60%. This effect can be traced to enhanced remineralization of organic matter that originates from the coast. These findings suggest that effects of land-based nutrients are not restricted to chemistry but extend to habitat capacity for multiple taxa of ecological and economic importance. Considerable uncertainty exists, however, in how this habitat compression translates to population-level effects.